Estudos em Eriocaulaceae Mart.: caracterização morfológica do tegumento e germinação de sementes - Leilane Carvalho Barreto (2012)
Eriocaulaceae is distributed by Africa and Americas, having as major diversitys center the Espinhaço Range, in Minas Gerais and Bahia states (Brazil). Recently, Comanthera L.B.Sm. was restablished from Syngonanthus Ruhland, and molecular phylogenetics analyses show them as monophyletic and sister groups. This study was done with Comanthera L.B.Sm. and Syngonanthus Ruhland (Eriocaulaceae Mart.) seeds and aimed to characterize the external morphology of Comanthera seeds using SEM to analyze its variations according to the currently phylogenetic hypothesis and verify the effect of different light exposures and gibberellin on seed germination. In SEM analysis it was observed that Comanthera seed coat shows a rough pattern, caused by different types of thickening of the periclinal faces, and the observed characteristics allow to separate the two subgenera, beyond corroborate the division established for the genres Syngonanthus and Comanthera, showing taxonomic and phylogenetic value. For the germination tests, seeds were submitted to the following treatments: continuous white light pulses, pulses of determined times for five days and light pulses with gibberellin solution 1000mg/L. The controls were done with seeds kept under continuous white light, 12h photoperiod, continuous dark and gibberellin solution 500 and 1000mg/L at light and dark. Results show that the three species need a long period of light exposure to germinate. For S. anthemidiflorus the germination was significantly higher (14,5 to 37,5%) in treatments with 30, 36 and 48h of light, and reached 60% in the treatment of 6h of light for five days. For S. verticillatus the highest germination obtained was 12,5%, in the treatment of 48h of light, and for C. bisulcata it was 15,3% with 4h of light for five days. The application of GA3 at 500 and 1000mg/L didnt promote germination of none of the seeds, not replacing the light requirement.